Selectionism Dominant: An Essay Review of Books by Basalla, Giere and Hull - Fleck, James (Research Centre for Social Science / University of Edinburgh, 1991)
In this paper, three books which apply evolutionary theories to the development of scientific or technical knowledge are reviewed. In each case, the biological example is used only metaphorically, but is exploited and developed rather differently. All the books focus on selection, rather than creation or generation processes. In their own different ways each book is a useful contribution, though none is a definitive synthesis. Together they provide considerable insight and a wealth of resources for understanding scientific and technical evolution. Their main limitations stem from the specific disciplinary perspectives within which each author works, along with the dominant emphasis on selection. These are also barriers to the elaboration of a fully satisfactory theory of scientific and technological evolution.
Keywords: scientific knowledge; technical knowledge; selectionism; selection; scientifc evolution; technical evolution